2022
DOI: 10.3390/ijms23105568
|View full text |Cite
|
Sign up to set email alerts
|

Intertwined Roles of Reactive Oxygen Species and Salicylic Acid Signaling Are Crucial for the Plant Response to Biotic Stress

Abstract: One of the earliest hallmarks of plant immune response is production of reactive oxygen species (ROS) in different subcellular compartments, which regulate plant immunity. A suitable equilibrium, which is crucial to prevent ROS overaccumulation leading to oxidative stress, is maintained by salicylic acid (SA), a chief regulator of ROS. However, ROS not only act downstream of SA signaling, but are also proposed to be a central component of a self-amplifying loop that regulates SA signaling as well as the intera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 139 publications
1
10
0
1
Order By: Relevance
“…The SA regulates the expression of various protective genes, primarily those responsible for the redox balance [169][170][171], which occurs not only upon pathogen attacks, but also probably during local heat and light stimuli [33,170,172].…”
Section: The Role Of Electrical Signals and Phytohormones In The Form...mentioning
confidence: 99%
“…The SA regulates the expression of various protective genes, primarily those responsible for the redox balance [169][170][171], which occurs not only upon pathogen attacks, but also probably during local heat and light stimuli [33,170,172].…”
Section: The Role Of Electrical Signals and Phytohormones In The Form...mentioning
confidence: 99%
“…These R proteins, which are generally located within the plant cell, may directly or indirectly recognize their related pathogen- encoded effectors activating ETI [ 1 , 2 ]. Both PTI and ETI are associated with the activation of defenses in the infected tissue, including the generation of reactive oxygen species (ROS) [ 3 ], increase in intracellular Ca 2+ concentrations, and activation of mitogen-activated protein kinases (MAPKs), to finally activate the expression of various defense-associated genes, synthesis of antimicrobial compounds, and accumulation of SA [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been reported that during defense responses against pathogens, increase in SA levels are preceded by apoplastic H 2 O 2 bursts 12 . Recent studies suggest that during plant response to biotic stress, the position where SA interacts with ROS signaling and ROS with SA signaling depends on the pathosystem and the origin of ROS 109 . In our study using pak choi plants, the multiplexed sensors reveal that both high heat and high light stimuli resulted in production of SA but at an earlier time point than the infection-triggered SA generation in pak choi.…”
Section: Discussionmentioning
confidence: 99%